Coping strategies in mothers with anxiety symptoms in single-parent female families of Ñuble, Chile - Massoglia Salas, Yvanna (2023)
The objective of this research was to understand the coping strategies of mothers of female single-parent families in the face of anxiety symptoms. We worked with a voluntary sample and by opportunity, semi-structured interviews focused on the problem were conducted in person and online with female heads of household of female single-parent families living in Ñuble, Chile. The results show different coping strategies adopted according to the life experience of each person, being social support one of the most used tools, together with avoidance and self-control with breathing techniques and self-instructions. It is observed that the belief system is a decisive support in coping with anxiogenic situations, as well as problem orientation and self-focus.